The Effectiveness of using Marhaban.Academy Cartoon Movie on TikTok to Improve Students’ Arabic Listening Skills - Azzahra, Qurrota Ayun; Inayah, Inayah; Zuhrudin, Achmad; Fihris, Fihris; Samra, Asma’ Na’im Jamil Abu (Universitas Ahmad Dahlan, 2025)
TikTok was selected as a learning platform due to its potential to foster an engaging educational environment that aligns with students' digital habits. This study aims to explore the use of the TikTok account marhaban.academy in teaching Arabic listening skills to students at Al-Azhar 29 BSB Islamic Preparatory School, as well as to evaluate its effectiveness. The research adopts a quasi-experimental quantitative design. Data were collected through observation and testing, including pre-tests and post-tests administered to eighth-grade students. The sample consisted of 50 students from classes VIII C and VIII D. Data were analyzed using descriptive statistics, normality and homogeneity tests, and an independent samples t-test. The hypothesis testing resulted in t count = 2.096, exceeding the critical value t table = 2.021 at a 0.05 significance level, indicating a significant improvement in students' listening skills. The findings demonstrate that TikTok, specifically marhaban.academy, serves as an effective medium for enhancing Arabic listening skills. Moreover, its popularity as a social media platform opens new opportunities for integrating Arabic language instruction across the four core skills—listening, speaking, reading, and writing—in schools, particularly at the junior high school level.